Diversidad del orden Odonata del Parque Central La Sabana, San José, Costa Rica (Repertorio Científico, 2024)
The Odonata order is made up of insects with totally aquatic habits in their larval state, in their adult state, they are recognized by their large compound eyes, short, barely visible antennae and two pairs of membranous wings. La Sabana is an important cultural and recreational area, which covers an area of 72 hectares in the center of San José. As part of the Sabana taxathon organized by Huella Verde-UNED Project of State Distance University, ICODER and Scotiabank, an insect count belonging to the Odonata order, was performed. The capture of the adults was carried out by means of an aerial entomological network, searching on the lagoon shore, in the vegetation and surrounding areas. Adults were placed in a hard-plastic box to be transported alive to the laboratory, where once there they were sacrificed and classified. The information obtained reflected 3 genera and 4 species of Coenagrionidae, as well as 6 genera and 7 species of Libellulidae